2018
DOI: 10.1088/1742-5468/aae2dd
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic critical properties of non-equilibrium Potts models with absorbing states

Abstract: We present extensive numerical simulations of a family of non-equilibrium Potts models with absorbing states that allows for a variety of scenarios, depending on the number of spin states and the range of the spin-spin interactions. These scenarios encompass a voter critical point, a discontinuous transition as well as the presence of both a symmetry-breaking phase transition and an absorbing phase transition. While we also investigate standard steady-state quantities, our emphasis is on time-dependent quantit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 43 publications
(147 reference statements)
4
5
0
Order By: Relevance
“…The expected voter critical behavior for this quantity (N f (t) ∼ t η GV with η GV = 0) suggests that N f (t) should be constant, and this has indeed been observed in a two-dimensional absorbing Ising model [22] as well as in linear voter models [23,35]. For our model, however, N f shows an early algebraic growth before it decreases as 1/ ln t at late times.…”
Section: B Phase Diagram Of the Microscopic Spin Modelsupporting
confidence: 69%
See 4 more Smart Citations
“…The expected voter critical behavior for this quantity (N f (t) ∼ t η GV with η GV = 0) suggests that N f (t) should be constant, and this has indeed been observed in a two-dimensional absorbing Ising model [22] as well as in linear voter models [23,35]. For our model, however, N f shows an early algebraic growth before it decreases as 1/ ln t at late times.…”
Section: B Phase Diagram Of the Microscopic Spin Modelsupporting
confidence: 69%
“…The scaling function f C only depends on the ratio of the two times t and s and decays algebraically for large arguments with an exponent λ. In [23] we showed that this aging scaling indeed prevails at a voter critical point, with the exponents taking on the values b = 0.120(5) and λ = 1.00 (2).…”
Section: A Quantitiesmentioning
confidence: 77%
See 3 more Smart Citations